Synthesis and Evaluation of the Antibacterial and Antioxidant Activities of Some Novel Chloroquinoline Analogs - Bayan Abdi; Mona Fekadu; Digafie Zeleke; Rajalakshmanan Eswaramoorthy; Yadessa Melaku (Journal of Chemistry)
Quinoline heterocycle is a useful scaffold to develop bioactive molecules used as anticancer, antimalaria, and antimicrobials. Inspired by their numerous biological activities, an attempt was made to synthesize a series of novel 7-chloroquinoline derivatives, including 2,7-dichloroquinoline-3-carbonitrile (5), 2,7-dichloroquinoline-3-carboxamide (6), 7-chloro-2-methoxyquinoline-3-carbaldehyde (7), 7-chloro-2-ethoxyquinoline-3-carbaldehyde (8), and 2-chloroquinoline-3-carbonitrile (12) by the application of Vilsmeier–Haack reaction and aromatic nucleophilic substitution of 2,7-dichloroquinoline-3-carbaldehyde. The carbaldehyde functional group was transformed into nitriles using POCl3 and NaN3, which was subsequently converted to amide using CH3CO2H and H2SO4. The compounds synthesized were screened for their antibacterial activity against Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, and Streptococcus pyogenes. Compounds 6 and 8 showed good activity against E. coli with an inhibition zone of 11.00 ± 0.04 and 12.00 ± 0.00 mm, respectively. Compound 5 had good activity against S. aureus and P. aeruginosa with an inhibition zone of 11.00 ± 0.03 mm relative to standard amoxicillin (18 ± 0.00 mm). Compound 7 displayed good activity against S. pyogenes with an inhibition zone of 11.00 ± 0.02 mm. The radical scavenging activity of these compounds was evaluated using 1,1-diphenyl-2-picrylhydrazyl (DPPH), and compounds 5 and 6 displayed the strongest antioxidant activity with IC50 of 2.17 and 0.31 µg/mL relative to ascorbic acid (2.41 µg/mL), respectively. The molecular docking study of the synthesized compounds was conducted to investigate their binding pattern with topoisomerase IIβ and E. coli DNA gyrase B. Compounds 6 (−6.4 kcal/mol) and 8 (−6.6 kcal/mol) exhibited better binding affinity in their in silico molecular docking against E. coli DNA gyrase. The synthesized compounds were also found to have minimum binding energy ranging from −6.9 to −7.3 kcal/mol against topoisomerase IIβ. The SwissADME predicted results showed that the synthesized compounds 5–8 and 12 satisfy Lipinski’s rule of five with zero violations. The ProTox-II predicted organ toxicity results revealed that all the synthesized compounds were inactive in hepatotoxicity, immunotoxicity, mutagenicity, and cytotoxicity. The findings of the in vitro antibacterial and molecular docking analysis suggested that compound 8 might be considered a hit compound for further analysis as antibacterial and anticancer drug. The radical scavenging activity displayed by compounds 5 and 6 suggests these compounds as a radical scavenger.